PENDAMPINGAN PENGUATAN INTERNALISASI USAHA UNTUK MENINGKATKAN DAYA SAING PRODUK MAKANAN TRADISIONAL DAERAH BOJONEGORO PADA USAHA SERABI KETAN - Hartiningsih Astuti; Joko Hadi Susilo; Albert Prana Adiguna; Dimas Surya Atmaja (Universitas Kadiri, 2026)
This community service program aims to strengthen the capacity and competitiveness of Serabi Ketan MSMEs in Trucuk District, Bojonegoro Regency through an integrated strategy that includes strengthening business identity, improving product quality and standardization, administrative arrangement, and brand digitalization. The program is designed to address the main problems of partners, namely weak branding, inconsistent quality, minimal business records, and the lack of utilization of digital technology. The activity stages include identifying needs, preparing interventions, intensive mentoring, and monitoring and evaluation to maintain sustainability. The results achieved are increased managerial capacity, a stronger brand identity, more standardized products, orderly administration, and a more optimal digital presence. This impact opens up opportunities for market expansion, increased competitiveness, and long-term business sustainability.